The role of galaxies and AGN in reionizing the IGM – III. IGM–galaxy cross-correlations at z ∼ 6 from eight quasar fields with DEIMOS and MUSE. Issue 2 (18th March 2020) - Meyer, Romain A; Kakiichi, Koki; Bosman, Sarah E I; Ellis, Richard S; Laporte, Nicolas; Robertson, Brant E; Ryan-Weber, Emma V; Mawatari, Ken; Zitrin, Adi
ABSTRACT: We present improved results of the measurement of the correlation between galaxies and the intergalactic medium transmission at the end of reionization. We have gathered a sample of 13 spectroscopically confirmed Lyman-break galaxies (LBGs) and 21 Lyman- α emitters (LAEs) at angular separations 20 arcsec ≲ θ ≲ 10 arcmin (∼0.1–4 pMpc at z ∼ 6) from the sightlines to eight background z ≳ 6 quasars. We report for the first time the detection of an excess of Lyman- α transmission spikes at ∼10–60 cMpc from LAEs (3.2 σ ) and LBGs (1.9 σ ). We interpret the data with an improved model of the galaxy–Lyman- α transmission and two-point cross-correlations, which includes the enhanced photoionization due to clustered faint sources, enhanced gas densities around the central bright objects and spatial variations of the mean free path. The observed LAE(LBG)–Lyman- α transmission spike two-point cross-correlation function (2PCCF) constrains the luminosity-averaged escape fraction of all galaxies contributing to reionization to f_esc _M_UV-12 = 0.14_-0.05^+0.28 (0.23_-0.12^+0.46) . We investigate if the 2PCCF measurement can determine whether bright or faint galaxies are the dominant contributors to reionization. Our results show that a contribution from faint galaxies (M_UV -20 (2σ) ) is necessary to reproduce the observed 2PCCF and that reionization might be driven by different sub-populations around LBGs and LAEs at z ∼ 6.